Control of myeloid-derived suppressor cell dynamics potentiates vaccine protection in multiple mouse models of Trypanosoma cruzi infection - Borgna, Eliana; Prochetto, Estefanía; Gamba, Juan Cruz; Vermeulen, Elba Mónica; Poncini, Carolina Verónica; Cribb, Pamela; Pérez, Ana Rosa; Marcipar, Iván; González, Florencia Belén; Cabrera, Gabriel (Frontiers in Immunology, 2024)
To date, there is no licensed vaccine against the protozoan parasite Trypanosoma cruzi (T. cruzi), the etiological agent of Chagas Disease. T. cruzi has evolved numerous mechanisms to evade and manipulate the host immune system. Among the subversive strategies employed by the parasite, marked increases in CD11b+ Gr-1+ myeloid-derived suppressor cells (MDSCs) in several organs have been described. We have reported that CD11b+ Gr-1+ cells are involved not only during infection but also after immunization with a trans-sialidase fragment (TSf) adjuvanted with a cage-like particle adjuvant (ISPA). Thus, the aim of this work was to gain control over the involvement of MDSCs during immunization to potentiate a vaccine candidate with protective capacity in multiple mouse models of T. cruzi infection. Here, we show that the Gr-1+ cells that increase during TSf-ISPA immunization have suppressive capacity over bone marrow-derived dendritic cells and CD4+ lymphocytes. Protocols using one or two doses of 5-fluorouracil (5FU) were employed to deplete and control MDSC dynamics during immunization. The protocol based on two doses of 5FU (double 5FU TSf-ISPA) was more successful in controlling MDSCs during immunization and triggered a higher immune effector response, as evidenced by increased numbers of CD4+, CD4+CD44+, CD8+, CD8+CD44+, CD11c+, and CD11c+CD8α+ cells in the spleen and lymph nodes of double 5FU TSf-ISPA mice as compared to 5FU-TSf-ISPA mice. In line with these results, the protective capacity of the double 5FU TSf-ISPA protocol was higher compared to the 5FU-TSf-ISPA protocol against high lethal doses of intraperitoneal infection with the Tulahuen T. cruzi strain. When cross-protective capacity was analyzed, the optimized protocol based on double 5FU TSf-ISPA conferred protection in several preclinical models using different discrete typing units (DTU VI and DTU I), different mouse strains (BALB/c and C57BL/6), different parasite doses (1000 to 20000), and routes of administration (intraperitoneal and intradermal).Developing vaccines that are currently lacking may require new strategies to further potentiate vaccine candidates. Results reported herein provide evidence that rational control of cells from the regulatory arm of the immune system could enhance a vaccine candidate with crossprotective capacity in multiple mouse models of T. cruzi infection.